2015
DOI: 10.1103/physrevd.91.045012
|View full text |Cite
|
Sign up to set email alerts
|

Bose-Einstein condensate strings

Abstract: We consider the possible existence of gravitationally bound general relativistic strings consisting of Bose-Einstein condensate (BEC) matter which is described, in the Newtonian limit, by the zero temperature time-dependent nonlinear Schr\"odinger equation (the Gross-Pitaevskii equation), with repulsive interparticle interactions. In the Madelung representation of the wave function, the quantum dynamics of the condensate can be formulated in terms of the classical continuity equation and the hydrodynamic Euler… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 124 publications
0
23
0
Order By: Relevance
“…This possibility has been intensively investigated in the literature (see [39] for a detailed discussion of the condensation processes in astrophysics), and the existence of stars with majority matter content in the form of a BEC cannot be excluded by present observations [40,41]. The matter inside a BEC star obeys a polytropic equation of state with polytropic index n = 1, and string-like objects composed of polytropic BEC matter, which resemble dark matter filaments, may also have formed in the early Universe [42]. For a class of self-gravitating matter models, with spherically symmetric field configurations, general scaling arguments were developed in [43,44] and applied to both the Einstein-Yang-Mills system and the Einstein sigma model.…”
mentioning
confidence: 86%
“…This possibility has been intensively investigated in the literature (see [39] for a detailed discussion of the condensation processes in astrophysics), and the existence of stars with majority matter content in the form of a BEC cannot be excluded by present observations [40,41]. The matter inside a BEC star obeys a polytropic equation of state with polytropic index n = 1, and string-like objects composed of polytropic BEC matter, which resemble dark matter filaments, may also have formed in the early Universe [42]. For a class of self-gravitating matter models, with spherically symmetric field configurations, general scaling arguments were developed in [43,44] and applied to both the Einstein-Yang-Mills system and the Einstein sigma model.…”
mentioning
confidence: 86%
“…It also becomes important when some types of the topological effects are needed suddenly by assigning an independent metric. In the context of modified theories of gravity, cosmic strings are investigated in f (R) gravity [58,60], teleparallel theories [61][62][63], brane worlds [64], Kaluza-Klein models [65], Lovelock Lagrangians [66], Gauss-Bonnet [67][68][69], Born-Infeld [70,71], bimetric theories [72], non-relativistic models of gravity [73], scalar-tensor theories [74][75][76][77][78][79], Brans-Dicke theory [80][81][82][83][84][85], dilation gravity [86,87], non-minimally coupled models of gravity [88], Mimetic gravity [89] and, recently, in the Bose-Einstein condensate strings [90]. However, the cosmic string is still unexplored in gravity's rainbow setting.…”
mentioning
confidence: 99%
“…In [59], it was suggested that BoseEinstein condensates (BECs), consisting of axionic dark matter or cosmological scalar fields [60], may have condensed to form string-like objects on cosmic scales. Such objects are capable of fulfilling the role of dark matter filaments [61].…”
Section: Discussion and Final Remarksmentioning
confidence: 99%